Dostosowania fiskalne w Polsce w latach 2004-2008 - Wojciechowska-Toruńska, Iwona (Fiscal Adjustments in Poland between 2004 and 2008, 2009)
The article presents the scale and the composition of fiscal adjustments in Poland between 2004 and 2008. The fiscal adjustments mainly resulted from an increase in public revenues (0.6%GDP) and an reduction in the government structural budget (0.7%GDP). There were two episodes of fiscal consolidation (2005, 2007) as the reductions in government structural deficit were at least 1% GDP per each year. Between 2004 and 2008 Poland kept its government primary budget deficit below the line of three percent GDP in order to match the Maastricht criteria and the Pact of Stability and Growth
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 39, T. 2, s. 362-370